Interplay between physical activity volume and intensity with modeled life expectancy in women and men: A prospective cohort analysis - Francesco Zaccardi; Alex V. Rowlands; Paddy C. Dempsey; Cameron Razieh; Joe Henson; Jonathan Goldney; Benjamin D. Maylor; Atanu Bhattacharjee; Yogini Chudasama; Charlotte Edwardson; Jari A. Laukkanen; Ulf Ekelund; et al. (Journal of Sport and Health Science)
Background: There is a lack of research examining the interplay between objectively measured physical activity volume and intensity with life expectancy. The purpose of the study was to investigate the interplay between objectively measured PA volume and intensity profiles with modeled life expectancy in women and men within the UK Biobank cohort study and interpret findings in relation to brisk walking. Methods: Individuals from UK Biobank with wrist-worn accelerometer data were included. The average acceleration and intensity gradient were extracted to describe the physical activity volume and intensity profile. Mortality data were obtained from national registries. Adjusted life expectancies were estimated using parametric flexible survival models. Results: 40,953 (57.1%) women (median age = 61.9 years) and 30,820 (42.9%) men (63.1 years) were included. Over a median follow-up of 6.9 years, there were 1719 (2.4%) deaths (733 in women; 986 in men). At 60 years, life expectancy was progressively longer for higher physical activity volume and intensity profiles, reaching 95.6 years in women and 94.5 years in men at the 90th centile for both volume and intensity, corresponding to 3.4 additional years (95% confidence interval (95%CI): 2.4–4.4) in women and 4.6 additional years (95%CI: 3.6–5.6) in men compared to those at the 10th centiles. An additional 10-min or 30-min daily brisk walk was associated with 0.9 (95%CI: 0.5–1.3) and 1.4 years (95%CI: 0.9–1.9) longer life expectancy, respectively, in inactive women; and 1.4 years (95%CI: 1.0–1.8) and 2.5 (95%CI: 1.9–3.1) in inactive men. Conclusion: Higher physical activity volumes were associated with longer life expectancy, with a higher physical activity intensity profile further adding to a longer life. Adding as little as a 10-min brisk walk to daily activity patterns may result in a meaningful benefit to life expectancy.